A one-step acidification strategy for sewage sludge dewatering with oxalic acid. (January 2020) - Chen, Na; Tao, Shuangyi; Xiao, Keke; Liang, Sha; Yang, Jiakuan; Zhang, Lizhi
Abstract: Sewage sludge dewatering is an efficient approach to reduce the volume of sludge for the subsequent disposal. In this study, a novel one-step acidification sludge dewatering method was developed with using oxalic acid as a conditioner. In laboratory-scale experiments with the dosage of 200 mg/g dry solid (DS), the normalized capillary suction time and the specific resistance to filtration were respectively decreased by 78.7% and 60.0% after 30 min of oxalic acid conditioning, much more efficient than those conditioned with sulfuric acid and hydrochloric acid at the same pH value. This superior dewatering performance was attributed to two factors. One was that oxalic acid could more efficiently promote the hydrolysis of polysaccharide, especially pectins, to release bound water. The other was that OA could dissolve more Fe 3+ and Al 3+, as well as form precipitate with Ca 2+ in sludge, which may act as flocculants or co-precipitator for the subsequent sludge particles coagulation. In pilot-scale experiments, the water content of oxalic acid conditioned sludge cake was reduced to 60% under the optimum conditions, while the reagent cost was as low as 110.0 USD/t DS. This work provides a cost-effective and easy-operated sewage sludge disposal technique, and also sheds light on the potential of oxalic acid in environmental waste treatment. Graphical abstract: Image 1 Highlights: OA was used as a novel conditioner for one-step acidification sludge dewatering. The normalized CST and SRF values were respectively decreased by 78.7% and 60.0% with OA conditioning. OA exhibited better sludge dewatering performance than common inorganic acids. OA could efficiently induce the hydrolysis of polysaccharide. OA could dissolve more Fe 3+ and Al 3+, as well as form precipitate with Ca 2+ in sludge for sludge particles coagulation.